Systematic Literature Review: Penerapan IoT Pada Alat Pengukur Suhu Tubuh Berbasis Mikrokontroler Sebagai Langkah Pencegahan Covid-19 - Muhamad Riyad Ariwibowo; Inayatul Ummah (Universitas Sarjanawiyata Tamansiswa, 2022)
The Covid-19 pandemic is a threat all over the world. This virus has an impact on economic, social, educational and health needs. Thus, various kinds of regulations were formed in order to reduce transmission from people who have the potential to be infected with the virus. With the implementation of social restrictions, every work area, tourist spot, and hospital will be checked for body temperature with a temperature measuring device. Therefore, the author makes the application of the SLR (Systematic Literature Review) method which aims to find out from previous researchers regarding the application of the internet of things to temperature measuring devices with a microcontroller onchip system that is used on these devices by screening related journals from the topic of the problem. Through SLR with the PICO approach method (Population, Intervention, Comparison, Outcome) the results show that the literature search is more specific by showing the division of two keywords in the search including, microcontroller as a body temperature gauge and internet of things (IoT) based body temperature meter. Thus, at the study identification stage it can be indicated on the inclusion and exclusion by reviewing the literature search that can be accepted and considered.